Class Library for Simulations of Passenger Transfer Nodes as Elements of the Public Transport System. (2017) - Naumov, Vitalii; Samchuk, Ganna
Abstract: Transfer nodes are essential elements of public transport systems which provide door-to-door transport services for passengers. Parameters of the technological processes in public transport systems are stochastic variables, thus, computer simulations are usually used for solving optimization problems of public transport. There is a number of simulation tools supporting decision-making in public transportation, but they don't provide the flexibility for solving the transfer nodes optimization problems. Authors present a library of classes implemented in Python, which could be used for computer simulations of public transfer nodes. The proposed software allows researchers to change technological parameters during simulation procedures and makes possible automatization of simulation experiments in the field of passengers' transportation.